2010
DOI: 10.1136/gut.2010.224436
|View full text |Cite
|
Sign up to set email alerts
|

Remodelling of extracellular matrix is a requirement for the hepatic progenitor cell response

Abstract: Failure of ECM remodelling after chronic fibrotic liver injury hinders the ability of the liver to activate HPCs. Laminin-progenitor cell interactions within the HPC niche are a critical for HPC mediated regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 56 publications
3
74
0
Order By: Relevance
“…Although paracrine signaling from the BMCs to the target organ has been suggested to underlie this phenomenon, such signaling has not been well characterized. Furthermore in the damaged liver any improvement in regeneration seen following BM injection may be an indirect phenomena secondary to the effects upon the surrounding matrix (23). Here we have demonstrated that a single infusion of unfractionated BMCs results in direct activation of a DR response in the undamaged liver.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Although paracrine signaling from the BMCs to the target organ has been suggested to underlie this phenomenon, such signaling has not been well characterized. Furthermore in the damaged liver any improvement in regeneration seen following BM injection may be an indirect phenomena secondary to the effects upon the surrounding matrix (23). Here we have demonstrated that a single infusion of unfractionated BMCs results in direct activation of a DR response in the undamaged liver.…”
Section: Discussionmentioning
confidence: 63%
“…However, a direct effect of macrophages upon the DRs or HPCs themselves has not been shown. The reduction of liver fibrosis itself is associated with improved hepatic regeneration (25) and the degree of matrix remodeling correlates to the magnitude of the DR response (23). Furthermore macrophages themselves are critical for the reduction in fibrosis (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Type IV collagen is also subject to extensive remodeling during fibrosis, and its quantity has been found to increase more than 10-fold during liver fibrogenesis (116,289). Variants of type IV collagen together with isoforms of laminin, nidogen, and perlecan are the main components of all basement membranes and form a sheet-like scaffold at the basal site of epithelia and endothelia and around interstitial cells (135,289) that maintain viability and differentiation of these cells (157,231). Other functions of this network are the provision of interaction sites for other ECM components, inflammatory cells, chemokines, cytokines, and important functions in cellular signaling (394).…”
Section: Fibrosis and The Ecmmentioning
confidence: 99%
“…A recent report has shown that activation of HPC might be linked up with ECM remodelling. Degradation of collagen I and subsequent laminin deposition seem to be important prerequisites for HPC activation and expansion [10]. Based upon these results it appears that a better understanding of the factors that govern HPC proliferation and the resultant ECM changes would provide clues to improve regeneration of liver cells in chronic liver disease.…”
Section: Activation Of Resident Regenerative Cells In the Liver By Inmentioning
confidence: 97%